2018
DOI: 10.3389/fphys.2018.01262
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as Therapeutic Agents and Targets

Abstract: It has recently been reported that thousands of covalently linked circular RNAs (circRNAs) are expressed from human genomes. circRNAs emerge during RNA splicing. circRNAs are circularized in a reaction termed “backsplicing,” whereby the spliceosome fuses a splice donor site in a downstream exon to a splice acceptor site in an upstream exon. Although a young field of research, first studies indicate that backsplicing is not an erroneous reaction of the spliceosome. Instead, circRNAs are produced in cells with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 165 publications
(309 reference statements)
0
113
0
2
Order By: Relevance
“…At present, it has been reported that overexpression of native protective circRNAs can be achieved by lentiviral or adenoviral vectors in vivo. They will encode mini-gene cassettes with exon(s), as well as the endogenous splice donor and acceptor sites, and flanking intronic inverted repeats that support RNA backfolding [43]. For instance, microinjection of circDLGAP4 lentivirus significantly ameliorates ischemic stroke outcomes [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it has been reported that overexpression of native protective circRNAs can be achieved by lentiviral or adenoviral vectors in vivo. They will encode mini-gene cassettes with exon(s), as well as the endogenous splice donor and acceptor sites, and flanking intronic inverted repeats that support RNA backfolding [43]. For instance, microinjection of circDLGAP4 lentivirus significantly ameliorates ischemic stroke outcomes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the delivery of circRNAs follows the existing methods for delivering therapeutic linear RNAs, as no specialized possibilities or physicochemical obstructions have yet been found associated with circularity. The strategies contain systemic injection into the vasculature, subcutaneous injection or depots, or local application [43].…”
Section: Discussionmentioning
confidence: 99%
“…The 5' and 3' end of exon or intron are jointed to construct the closed loop. The alternative splicing for pre-mRNA transcript could yield diverse circRNAs subtype 10,11 . In human cancer, circRNA could diffusely modify the tumor progression by post-transcriptional regulation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a novel class of transcribed RNAs found in Archaea [76] and a variety of eukaryotic organisms [77,78]. High-throughput RNA-sequencing has shown that at least 20% of currently active genes express circRNAs [79]. Usually, circRNAs are formed through "back-splicing" of the precursor messenger RNAs (pre-mRNAs), in which a downstream splice donor is joined to an upstream splice acceptor via a 3'→5' phosphodiester bond [80][81][82].…”
Section: Circular Rnasmentioning
confidence: 99%
“…CircRNAs not only represent the possible targets for RA (see above) but also may be used as effectors targeting miRNA/siRNA [79]. CircRNAs are much more stable than mRNAs and may produce proteins.…”
Section: Circular Rnamentioning
confidence: 99%